Correction: An antibody screen of a Plasmodium vivax antigen library identifies novel merozoite proteins associated with clinical protection. - Camila T França; Jessica B Hostetler; Sumana Sharma; Michael T White; Enmoore Lin; Benson Kiniboro; Andreea Waltmann; Andrew W Darcy; Connie S N Li Wai Suen; Peter Siba; Christopher L King; Julian C Rayner; et al. (PLoS Neglected Tropical Diseases)
[This corrects the article DOI: 10.1371/journal.pntd.0004639.].